Theoretical modeling and experimental validation of the centrifugal softening effect for high-efficiency energy harvesting in ultralow-frequency rotational motion. (1st May 2021) - Mei, Xutao; Zhou, Ran; Fang, Shitong; Zhou, Shengxi; Yang, Bo; Nakano, Kimihiko
Highlights: Centrifugal softening effect is an effective way efficiency energy harvesting (less than 2 Hz). A novel theoretical model to explain the centrifugal softening effect is derived. The Kc1 coefficient reveals the mechanism of the centrifugal softening effect. The generated RMS voltage more than 3 V is sufficient to power a wireless sensor . Abstract: Recently, the energy harvesting technique has been a promising way to power low-powered wireless sensor nodes. Considering the advantages of rotational motion, various energy harvesters were designed and investigated for rotational energy harvesting. Among these previous studies, it has been demonstrated that the centrifugal force plays an important role in the dynamic response and the generated power of a piezoelectric energy harvester (PEH). As a result, this paper aims to reveal the mechanism of the centrifugal softening effect caused by the centrifugal force, and by which to enhance the energy harvesting performance in ultralow-frequency rotational motion (less than 2 Hz). Therefore, an inverse PEH configuration in rotational motion is proposed in this paper. A compressive theoretical model describing its dynamic response and output voltage is derived according to Lagrange equation and other assumptions. An experimental setup is established to verify the proposed theoretical model and to investigate the influence of the centrifugal softening effect on the output voltage. According to the experimental results, the root-mean-square (RMS) output voltage of the proposed PEH with the centrifugal softening effect reaches 4 V, which is improved over 100% under the rotational speed range of 75–120 rpm (1.2–2 Hz) compared with the forward PEH configuration. Furthermore, such a significant enhancement due to the centrifugal softening effect is theoretically explained via the derived theoretical model. Overall, the centrifugal softening effect is markedly beneficial for energy harvesting in ultralow-frequency rotational motion, and the derived theoretical model has been validated by the experiments to be effective. This study provides the theoretical and experimental guidance for the further research and applications of the centrifugal softening effect.